Effects of Tea Polyphenols and Microporous Packaging Treatment on Storage and Preservation of Leaf-Vegetable Sweet Potatoes - Linjiang Pang; Xuefen Lou; Ximing Xu; You Lv; Qingyun Sun; Chengyuan Hu; Yueming Zhu; Xinghua Lu; Chao Xiang; Yuge Guan; Jiyu Cheng; Guoquan Lu; et al. (Foods)
Leaf-vegetable sweet potatoes incurred significant losses during storage, which resulted in a shortened shelf life and reduced commercial value. This study investigated the effects of tea polyphenols (TPs) fumigation and microporous packaging (MP) during 10 days at 10 °C and 90–95% RH. The results indicated that the preservation effects followed the order TP + MP > MP > TP > CK, with the TP + MP treatment effectively controlling the degradation rate of chlorophyll and delaying leaf yellowing. In addition, TP + MP treatment increased the activity of antioxidant enzymes, especially catalase (CAT) and ascorbate peroxidase (APX), and also enhanced non-enzymatic systems (flavonoids, total phenolics, and ascorbic acid). Pearson’s correlation analysis showed a positive correlation between the decline in postharvest quality of leaf-vegetable sweet potatoes and the increase in reactive oxygen species (ROS) levels. This study provided a robust theoretical and technical foundation for the development of effective postharvest preservation strategies for leaf-vegetable sweet potatoes.